Blood transfusion needs among obstetric patients in a tertiary care hospital: a prospective observational study - ., Renuka; S., Shridevi A.; Patil, Gayathri L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Pregnancy possess a special challenge as immune responses in pregnant and non-pregnant states are different. The objectives of this study were to analyze the various indications for blood and blood component transfusion in obstetric patients. To study the prevalence and indications for blood transfusion among obstetric patients. To evaluate the various risk factors among these women. To study the role of antenatal visits in patients requiring blood transfusion Methods: A prospective observational study will be undertaken over a period of one year from July 2018 to June 2019 in Department of Obstetrics and Gynecology at SSIMS and RC, Davangere. This study was conducted on pregnant women and immediate postpartum patients (up to 7 days after delivery) admitted in Department of Obstetrics and Gynecology and requiring blood and blood component therapy. Statistical analysis will be performed using Chi square test and Student’s t test. Results: During study period out of 5486 patients 543 patients required blood transfusion. The incidence of blood transfusion is 9.89%. The indications for blood and blood product transfusion observed in our study were anemia, obstetric hemorrhage, thrombocytopenia, disseminated intravascular coagulopathy, ruptured ectopic, incomplete abortion, complete abortion and hydatidiform mole. Anemia in pregnancy was the most common indication and was observed in 217 cases (39.96%) followed by postpartum hemorrhage, which was seen in 117 cases (21.54%). The incidence of transfusion reactions was 5.34% in our study. Conclusions: A proper knowledge of blood and blood product transfusion is needed to make it available for people who are actually in need and also to decrease the economic burden. Regular Antenatal checkups should be given more importance in order to maximize the hemoglobin level at the time of delivery and to screen out the high-risk patients. Active management of the third stage of labor is required to minimize the blood loss. Anemia followed by obstetric hemorrhage still persists to be a major cause for blood and blood product transfusion.